Saving Humanity: Despair and Death as Pedagogical Challenges while Caring about Human Existence - Julita Orzelska (Nicolaus Copernicus University in Toruń, 2021)
The concepts analysed in this paper pertain to despair and death, since these are insufficiently present in pedagogical narrations. Despair and death, which accompany our existential experience throughout our lives, are most frequently treated one-sidedly, pejoratively, and presented as an expression of human evil. The thoughts of Paul Tillich, Viktor Frankl, Vittorino Andreoli and Krystian Lupa open a space for understanding despair and death as existential challenges a person needs to be capable of facing and should treat as valuable experience; an experience which creates an opportunity for a new dimension in our own appreciation of life. For this reason, an existentially oriented education seems to enable serious thought about a person in the context of their entire life.